Linkages among selected Western and Asian stock markets / Noraini Aminudin - Aminudin, Noraini (Research Management Institute (RMI), 2011)
This empirical research investigates the international inter-relatedness among a number of national equity markets. These markets are from Malaysia, Singapore, Thailand, Japan, Korea, Taiwan, Australia, Hong Kong, Indonesia, the United States, the United Kingdom, the Philippines, France, Germany, Denmark, Switzerland, Spain, Canada and Belgium. These markets were chosen as they include both emerging markets as well as well-established markets. Some authors such as Rhee and Chang (1991) studied the performance of the Pacific Basin stock markets (Australia, Japan, Hong Kong, Singapore, Malaysia, Korea, Taiwan and Thailand) and of the top five markets in the world (Japan, United States, United Kingdom, France and Germany). Together, these markets represent around 90% of the world's stock market capitalization. As the title implies, this study examines the structure of international stock market linkages. Knowledge of international stock market linkages, or interdependencies, is useful for international portfolio diversification, where investors can try to reduce a portion of the risk.